2002
DOI: 10.1182/blood.v100.8.2703
|View full text |Cite
|
Sign up to set email alerts
|

Negative prognostic value of glutathione S-transferase(GSTM1 and GSTT1) deletions in adult acute myeloid leukemia

Abstract: Glutathione S-transferases (GSTs) are enzymes involved in the detoxification of several environmental mutagens, carcinogens, and anticancer drugs. GST polymorphisms resulting in decreased enzymatic activity have been associated with several types of solid tumors. We determined the prognostic significance of the deletion of 2 GST subfamilies genes, M1 and T1, in patients with acute myeloid leukemia (AML). Using polymerase chain reactions, we analyzed the GSTM1 and GSTT1 genotype in 106 patients with AML (median… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
1
7

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(67 citation statements)
references
References 25 publications
2
57
1
7
Order By: Relevance
“…When we examine the association between pediatric and adult patients, we found that adult ALL group showed a decrease in the frequency of GSTT1 null genotype (OR ¼ 0.2, P ¼ 0.04). Although different studies reported associations between lack of activity of the GSTT1 enzyme and risk of developing leukemia [35,37,38], our finding show different risks because of the number of samples in the adult ALL group, which was too small to support an association. We observed the GSTM1 null genotype frequencies increased in ALL (62.6%) and AML (68.1%) patient groups compared to controls (55.0%).…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…When we examine the association between pediatric and adult patients, we found that adult ALL group showed a decrease in the frequency of GSTT1 null genotype (OR ¼ 0.2, P ¼ 0.04). Although different studies reported associations between lack of activity of the GSTT1 enzyme and risk of developing leukemia [35,37,38], our finding show different risks because of the number of samples in the adult ALL group, which was too small to support an association. We observed the GSTM1 null genotype frequencies increased in ALL (62.6%) and AML (68.1%) patient groups compared to controls (55.0%).…”
Section: Discussioncontrasting
confidence: 91%
“…The homozygous CYP1A1*2A genotype frequency was decreased in our ALL patients, whereas it was increased in AML patients, but the differences were not statistically different (Tables I and II). CYP1A1 variants result in increased enzyme activity or inducibility such as *2, *3, and *4 are found associated with the leukemia development [37,38], and the risk of leukemia needs to be evaluated with the studies of these additional CYP1A1 variants.…”
Section: Discussionmentioning
confidence: 99%
“…GST polymorphisms are widely spread in the population, with a large proportion of individuals presenting with homozygous deletion of the genes. There are only a few reports on AML susceptibility and it has been postulated that CYP and GST polymorphisms resulting in decreased enzymatic activity have been associated with an increased risk of cancer, including leukemia [6][7][8]. Also, xenobiotic metabolizing enzymes polymorphisms may influence the prognosis of AML and Hodgkin's lymphoma, as previously shown [6].…”
Section: Introductionmentioning
confidence: 92%
“…31,32 Furthermore, single and combined deletions at both of these gene loci have been linked to enhanced drug resistance and poor clinical outcome in patients with carcinomas of the ovary 33 and the lung, 34 and also in patients with leukemia. 35,36 Some of these discrepancies may be attributable to methodologic issues, such as differences in study design, study population, sample size, and genotyping methods; differences in GST expression in target tissue; or differences in chemotherapy regimens used.…”
Section: Discussionmentioning
confidence: 99%